(untitled) (Journal of Medical & Health Sciences Review, 2025)
The increasing emergence of multidrug-resistant (MDR) bacteria has become a major global healthcare challenge, limiting the effectiveness of conventional antibiotics. This study aimed to evaluate the antibacterial potential of clove oil against selected MDR bacterial strains isolated from clinical samples. A total of clinical specimens, including blood, urine, pus, and sputum, were collected from patients at different tertiary care hospitals. The isolated organisms were identified as Staphylococcus aureus, Escherichia coli, and Pseudomonas aeruginosa using Gram staining and a series of biochemical tests such as oxidase, catalase, citrate, urease, and indole tests. Gram-positive cocci (S. aureus) appeared purple under microscopic examination, while Gram-negative rods (E. coli and P. aeruginosa) stained pink. The antimicrobial activity of clove oil was assessed through the agar well diffusion method. Different concentrations of clove oil (20 µL, 40 µL, 60 µL, 80 µL, and 100 µL) were tested to observe the zone of inhibition against each bacterial strain. The results demonstrated a concentration-dependent antibacterial effect. The maximum inhibitory zone for S. aureus was recorded at 10.5 mm, P. aeruginosa at 15 mm, and E. coli at 11 mm at the highest concentration of 100 µL. At lower concentrations, the antibacterial activity was significantly reduced, with E. coli showing no inhibition at 20 µL. These findings suggest that clove oil possesses significant antibacterial properties against MDR bacteria and can serve as a promising alternative or complementary approach to combat antibiotic-resistant infections. Further research and clinical trials are necessary to validate its efficacy and safety for therapeutic use.